P033: Clinical and laboratory characteristics of patients presenting to a tertiary care centre emergency department with invasive Group A Streptococcus infections. (May 2019) - Dudar, K.; Littlefield, S.; Garnett, M.
Abstract : Introduction : According to the Public Health Agency of Canada, the rate of invasive Group A Streptococcus (iGAS) has more than doubled since it first became a notifiable disease in 2000. Our objectives were to describe the clinical and laboratory characteristics of iGAS in a geographic area that sees a relatively high volume of cases annually.Methods : We conducted a retrospective chart review of all adult and pediatric patients presenting to the Thunder Bay Regional Health Sciences Centre Emergency Department from January 2016 to December 2017 with a hospital discharge diagnosis of iGAS infection using ICD-10 codes. Patient demographics, host characteristics, triage vital signs, laboratory values, culture sites, and disposition were analyzed using univariate and bivariate statistics.Results : Forty-five cases of iGAS were identified over 2 years, with a mean age of 45 years (SD 18). The most prevalent associations were male sex (69%), diabetes mellitus (44%), current or previous alcohol abuse (38%), and current or previous intravenous drug use (33%). Prevalence of iGAS was roughly two times the national average in 2016 (11.5 per 100, 000) and four times the national average in 2017 (25.5 per 100, 000). Mean triage vital signs included a systolic blood pressure of 126 mmHg (SD 24), diastolic blood pressure of 73 mmHg (SD 16), temperature of 37.3°C (SD 1.4), oxygen saturation of 97% (SD 2), heart rate of 113 beats per minute (SD 22), and respiratory rate of 22 breaths per minute (SD 7). Mean laboratory values revealed a white blood cell count of 17, 500 cells/μL (SD 9, 800) and C-reactive protein of 243 mg/L (SD 144). A higher Laboratory Risk Indicator for Necrotizing Fasciitis (LRINEC) score was positively correlated with longer hospital length of stay (r = 0.46, p < 0.01).Conclusion : Despite its morbidity and mortality, iGAS infections often present insidiously with only mild abnormalities in triage vital signs, and require a high index of suspicion by the emergency physician for a prompt diagnosis, particularly in at-risk populations such as patients with diabetes mellitus or those who misuse alcohol or drugs.